Experimental measurements of water molecule binding energies for the second and third solvation shells of [Ca(H₂O)n]2+ complexes - Bruzzi, E.; Stace, Anthony J. (Royal Society, 2017)
Further understanding of the biological role of the Ca2+ ion in an aqueous environment requires quantitative measurements of both the short and long range interactions experienced by the ion in an aqueous medium. Here we present experimental measurements of binding energies for water molecules occupying the second and, quite possibly, the third solvation shell surrounding a central Ca2+ ion in [Ca(H2O)n]2+ complexes. Results for these large, previously inaccessible, complexes have come from the application of finite heat bath theory to kinetic energy measurements following unimolecular decay. Even at n = 20 the results show water molecules to be more strongly bound to Ca2+ than would be expected just from the presence of an extended network of hydrogen bonds. For n > 10, there is very good agreement between the experimental binding energies and recently published DFT calculations. Comparisons are made with similar data recorded for [Ca(NH3)n]2+ and [Ca(CH3OH)n]2+ complexes.